Pemberian Hak Asuh Anak Kepada Ibu Pasca Perceraian (Studi Kasus Putusan Pengadilan Negeri Sumber Nomor 32/PDT.G/2020/PN Sbr) - Irawan, Cindy Haura (Wajah Hukum, 2024)
Custody of minor children will actually be received by the biological mother. However, in the case in the Decision of the Sumber District Court Number 32/Pdt.G/2020/PN Sbr., there is a fact that post-divorce child custody should be given to the biological father. In this case, although there is strong evidence to support the granting of custody to the father and the mother's living environment is considered unfavorable based on the available evidence. The child's welfare must still be prioritized in determining whether care is carried out by the mother or father. This is because the emotional bonds that children have greatly influence their development in life. The aim of this research is that the author wants to find out whether the factors in granting child custody to the mother in the case of the Sumber District Court Decision Number 49/Pdt.G/2019/PN Sbr can be justified according to the laws and regulations regarding marriage in Indonesia. This research uses a legislative approach using secondary data in the form of primary legal materials and secondary legal materials. The author collected data by conducting a literature study. The research data that has been obtained will be analyzed qualitatively. The result of the discussion of this research is that child custody is still given to the mother because the thing that is considered is not about events before or after the divorce that influence it, but about choosing a figure who makes them feel safe and prosperous, even in an undesirable situation.